Effectiveness of Oxytocin Massage in Spontaneous Post Partum Mothers to Increase Breast Milk Production - Roslianti, Elis; Nalaratih, Ayu; Oktriani, Herni; Fitriani, Ade; Lismayanti, Lilis; Ridla Fauzi, Aulia (Yayasan Inspirasi El Burhani, 2022)
Objective: To determine the effectiveness of oxytocin massage on postpartum mothers to increase lactation. Method: The method used is a descriptive design in the form of a case study with a maternity nursing care process approach which includes assessment, diagnosis, planning, implementation and evaluation. The subjects used in this study were clients who had problems with ineffective breastfeeding in Lotus Room 2 BLUD Banjar City General Hospital. This data collection technique includes interviews, observations, physical examinations and documentation studies. Result: Evaluation of the administration of oxytocin massage therapy on the issue of breastfeeding is proven in clients who routinely do oxytocin massage after 4 days of increased milk production, marked by how often the baby is breastfed and how long he sleeps after being breastfed. Conclusion: Oxytocin massage therapy has been proven to be effective for smoothing and increasing the production of the hormones oxytocin and prolactin, which function to smooth out breast milk.